Tensor categories arising from the Virasoro algebra - Creutzig, Thomas; Jiang, Cuipo; Orosz Hunziker, Florencia; Ridout, David; Yang, Jinwei (Advances in Mathematics, 2021)
We show that there is a braided tensor category structure on the category of C1-cofinite modules for the (universal or simple) Virasoro vertex operator algebras of arbitrary central charge. In the generic case of central charge c=13−6(t+t−1), with t∉Q, we prove semisimplicity, rigidity and non-degeneracy and also compute the fusion rules of this tensor category.
CRIS-Team Scopus Importer:2024-06-24
Keywords: Non C; Universal Virasoro vertex algebras; Vertex tensor categories; Virasoro algebra